Challenges for Central Banking in the development of a stabilization program - Arista, José (1989)
The paper analyzes the main problems that the Central Bank has to deal during the transition period of high to low inflation. In the first part, the core of our discussion is related with the policy of monetary accommodation when the target is a high level of real exchange rate. Then, we present two ways in orden to overcome the wealth transfer problem produced by the hangovers of past states of expectations. Finally, we point out the puzzles generated by the usual behavior of the nominal interest rate during the stabilization period.